Wandering Son. Volume six - Shimura, Takako, 1973- (Fantagraphics Books, 2013)
Nitori, the boy who wants to be a girl, and Chiba, the girl who is crushing on him, write an adaptation of "Romeo and Juliet," with Chiba hoping to play Romeo with Nitori as Juliet--but Nitori would rather have Takatsuki, the girl who wants to be a boy, in the role of Romeo.